The feared five fungal infections in kidney transplant recipients: A single‐center 20‐year experience. Issue 7 (19th June 2018) - Parajuli, Sandesh; Wick, Alexandra; Pandeya, Sameer; Astor, Brad C.; Smith, Jeannina; Djamali, Arjang; Mandelbrot, Didier A.
Abstract: Invasive fungal infections are a feared complication in kidney transplant recipients (KTRs). Here we present the University of Wisconsin experience with 5 invasive fungal infections—aspergillosis, cryptococcosis, histoplasmosis, blastomycosis, and coccidioidomycosis—in KTRs transplanted between 01/01/1994 and 06/30/2014. During this period, there were 128 cases of fungal infections; aspergillosis was the most common (72), followed by cryptococcosis (29), histoplasmosis (14), blastomycosis (10), and coccidioidomycosis (3). The mean interval from transplant to fungal infection was 3.19 ± 3.58 years (range 5 days‐15.8 years). By 6 months postinfection, there were 53 (41%) graft failures and 24 (19%) deaths. Graft failure occurred in 46%, 38%, 21%, 40%, and 67% of patients with aspergillosis, cryptococcosis, histoplasmosis, blastomycosis, and coccidioidomycosis, respectively. Anti‐thymocyte globulin (ATG) induction (HR, 1.49; 95% CI, 1.03‐2.16; P  = .04), diabetes (HR, 1.53; 95% CI, 1.05‐2.21; P  = .03), and age (HR, 1.47; 95% CI, 1.27‐1.70; P  ≤ .001) were associated with an increased risk for infection in univariate analysis. Multivariate adjustment retained ATG induction and older age. A large proportion of kidney transplant recipients with invasive fungal infections suffer graft failure within 3 years. Preventive, therapeutic, and monitoring strategies are needed to improve graft and patient outcomes.